EFEK PROTEIN SEMPURNA DAN TIDAK SEMPURNA TERHADAP BERAT BADAN DAN ALBUMIN TIKUS - hermawati Hermawati; Abdul Salam; Sabaria Manti Battung (Departement of Nutrition, Faculty of Public Health, Hasanuddin University, Makassar, 2019)
Introduction: Protein is the trigger for the occurrence of obesity and changes in albumin levelsin weight gain. Obesity is one of the most serious public health challenges in the 21st century. Objektive:This study aimed to determine the effects of high-protein complete and uncomplete diet to weight gainand albumin levels in wistar rats. Methods: The samples used 15 wistas rats which were dividedrandomly into 3 groups, each consisting of 5 tails weighing 150-200 g and in healthy condition.Standard AD 2 feed was given to the control group, intervention feed given to complete protein andsoybean intervention feed protein group was uncomplete. The study was conducted for 6 weeks, 2 weeksof adaptation and 4 weeks of intervention. The research method used a true experiment with arandomized control group pretest-posttest desigen. The data collected consisted of weighing the bodyand measuring the rat albumin level which was carried out 2 times before the intervention day 0 andafter the intervention of the 28th day. Data analysis used One Way ANOVA statistical test followed byPost Hoc Tukey and Paired Sample Test was accepted if p <0.05. Results: The results of measurementsof weight gain obtained before the intervention were not significant with p = 0.790 and measurementsafter intervention obtained significant results with a value of p = 0.014, as well as examination ofinsignificant albumin levels before intervention with p = 0.251 and significant on examination after theintervention with a value of p = 0.003. Conclusion: It It can be concluded as an intervention afterweight gain and albumin levels.